PanScales showers for hadron collisions: all-order validation - Melissa van Beekveld; Silvia Ferrario Ravasio; Keith Hamilton; Gavin P. Salam; Alba Soto-Ontoso; Gregory Soyez; Rob Verheyen (Journal of High Energy Physics, 2022)
Abstract We carry out extensive tests of the next-to-leading logarithmic (NLL) accuracy of the PanScales parton showers, as introduced recently for colour-singlet production in hadron collisions. The tests include comparisons to (semi-)analytic NLL calculations of a wide range of hadron-collider observables: the colour-singlet boson transverse momentum distribution; global and non-global hadronic energy flow variables related to jet vetoes and analogues of jettiness distributions; (sub)jet multiplicities; and observables sensitive to the DGLAP evolution of the incoming momentum fractions. In the tests, we also include an implementation of a standard transverse-momentum ordered dipole shower, to establish the size of missing NLL effects in such showers, which, depending on the observable, can reach 100%. This paper, together with [1], constitutes the first step towards process-independent NLL-accurate parton showers for hadronic collisions.